Horizontal scalability analysis in a hbase cluster - Dos Santos, Cedryk Augusto [UNESP] (2020)
Horizontal Scalability allows resources to be distributed by the addition of nodes, being made more flexible by the NoSQL Database. This work evaluates the horizontal scalability potential of a Hbase Database cluster, through a benchmarking in several scenarios, an ideal scenario is obtained, to verify the efficiency and availability of applications regardless of storage demand, operations and nodes addition. The results indicate that scalability is more evident, except in scan operations, in sets of 100,000 and 1,000,000 records, in increasing the number of nodes from 1 to 2 and from 2 to 3. In the search operations, there is no improvement from the additional nodes.